The ANALISIS TINGKAT KEMATANGAN TATA KELOLA TI PADA SISTEM INFORMASI AKADEMIK MENGGUNAKAN FRAMEWORK COBIT 5 DI SMAN 1 PEMULUTAN - Agusnita, Andina Rahayu; Sutabri, Tata (LPPM UNIVERSITAS BINA INSAN, 2023)
SMAN 1 Pemulutan is one of the schools that implements IT governance in the Academic Information System. Academic SI is an information system used by SMAN 1 Pemulutan in implementing learning for students. Therefore, it is necessary to measure the maturity level using COBIT 5. Problem formulation, how to classify problems into statements according to COBIT 5 and how to determine and measure the maturity level of IT governance. The limitations of the research were only carried out on the Academic SI of SMAN 1 Pemulutan, only using COBIT 5 MEA domains and the research object was only on students and related parties. The aim of the research is to determine the maturity level of Academic SI IT governance in the MEA domain and to find out recommendations for improvement at SMAN 1 Pemulutan. The MEA domain consists of 3 sub domains. Researchers used a questionnaire instrument. The sample used was 30 people. The MEA01 maturity level value is 3.2; MEA02 is 3.3 and MEA03 is 3.3. So the average MEA maturity level value is 3.3, namely Established Process. The results of the recommendations from MEA01 establish guidelines and standard SOPs for implementing monitoring and evaluation of Academic SI, there is a need for monitoring from leadership regarding the duties of each Stakeholder. MEA02 develops control/supervision process mechanisms and quality assurance standards for Academic SI. MEA03 reviews and creates standard guidelines and SOPs regarding changes to Academic SI based on external changes.